2022
DOI: 10.4491/eer.2021.545
|View full text |Cite
|
Sign up to set email alerts
|

Using nano-magnesium oxide/bentonite composite for cadmium removal from industrial wastewater

Abstract: Nowadays, the removal of toxic heavy metals from industrial wastewater is a long standing problem due to the industrial progress worldwide. This study mainly focused on the production of a novel nMgO-bentonite nanocomposite using sol–gel method to enhance Cd ions removal from industrial wastewater. The nMgO-bentonite nano-composite was characterized for structural morphology and presence of functional groups using SEM/EDS, XRD and FTIR analysis. Cadmium sorption equilibrium and kinetic data were well fitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The Monod model is used to represent the relationship between the limiting substrate concentration and the specific growth rate using Eqs. ( 21) and (22).…”
Section: Biodegradation Kinetics: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Monod model is used to represent the relationship between the limiting substrate concentration and the specific growth rate using Eqs. ( 21) and (22).…”
Section: Biodegradation Kinetics: Theoretical Considerationsmentioning
confidence: 99%
“…In recent years, researchers have shown an increasing interest in metal oxides, specifically magnesium oxide nanoparticles (nMgO), due to their beneficial characteristics, such as high specific surface area, low density, nontoxicity, affordable production, and superior physical properties. According to a study by Elkhatib et al [22], mesoporous MgO nano-sheets exhibited the maximum adsorption capacity of 200 mg/g for Cd(II) removal from industrial wastewater. Bentonite, a type of clay mineral that contains mainly montmorillonite, has also gained popularity in various industries due to its abundance in nature, low cost, large surface area, good chemical and mechanical stability, and its ability to exchange cations with those found in aqueous solutions of organic or inorganic salts, as reported by Aichour and Zaghouane [23].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the surface feature of magnesium nanoparticles, P. Gabriela et al (2022), A.E. Elsayed et al (2023) consider it appropriate to use them for binding unreacted formaldehyde in the manufacture of wood composite materials, which will contribute to the environmental friendliness of both the technological process and products during operation. This modification of wood-composite materials makes it possible to obtain materials with additional characteristics and added value (M. Shvets et al, 2020).…”
Section: Spectrummentioning
confidence: 99%
“…In all studied sorbents, Cd sorption was quite rapid in the rst 30 minutes as 99% of Cd was sorbed and followed by slow sorption step. Elkhatib et al 32 reported that the rapid Cd adsorption is a surface phenomenon where vacant sites on sorbent surface are rapidly lled in the early stage and followed by diffusion and slow migration. kinetics modeling.…”
Section: Speci C Surface Areamentioning
confidence: 99%